Accelerating the process development of innovative food products by prototyping through 3D printing technology. (April 2023) - Derossi, A.; Corradini, M.G.; Caporizzi, R.; Oral, M.O.; Severini, C.
Abstract: Discoveries and applications of 3D food printing (3DFP) keep growing with a large set of outcomes, such as the development and optimization of novel edible inks and post-printing processes. However, the main principle at the core of 3D printing, i.e. Rapid Prototyping, hasn't received the deserved attention. Thus, beyond generating innovative food products, this study emphasizes the opportunities and benefits of 3DFP for food prototyping. Several cereal-based snacks were generated, and their corresponding baking kinetics were monitored considering changes in the most important characteristics of the product, its impact on productivity and potential safety concerns. The prototypes had two shapes (cylindrical and cubical), three infill levels (30, 60, and 100%) and two infill paths (grid and gyroid). Moisture content was satisfactorily described by using a modified version of a logistic model (r > 0.98), enabling to estimate and, then, successfully validating the baking time to get a moisture content lower than 0.1 g H2 O/g dry basis (d.b.). 3D printed structures with 30% infill exhibited a significant reduction in baking time (from 16.5 to 19.2 min) against not only those with 60% infill but also the control, which needed 38.6 min of baking; this emphasizes the benefits of controlled pattern designs on energy consumption and increasing hourly production. Furthermore, acrylamide formation was estimated to be between 39 and 91% lower than in the control samples after receiving comparative thermal treatments. 3DFP may be used as an important prototyping tool, extending and accelerating the manufacturing of food products with economic, nutritional/toxicological, societal, and environmental benefits. Highlights: 3D Printing was used to prototype biscuits with different morphologies and properties. 3D printing can be used to design shapes and internal structures that reduce baking time. A significant reduction of baking time was obtained for all 3D printed biscuits. 3D printed samples exhibited lower acrylamide content estimations than the control.